Analysing The Labour Use Pattern And Efficiency In Urban Dairy Farms Of Tamil Nadu - Pandian, A. Serma Saravana; Vetrivel, D.; Shree, J.Shilpa; Raja, M.Boopathy; Siddharth , M. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was under taken in three urban areas namely Chennai (Tambaram), Erode and Vellore of Tamil Nadu with the objectives of analysing the pattern of labour use and assessing the factors influencing labour use efficiency in the dairy farms. A total of 90 dairy farms were selected for the study by simple random sampling technique. From the selected farms information relating to various aspects of dairy farming was collected by survey method with a well-designed and pre-tested interview schedule. To determine factors contributing to the observed labour-use efficiency, the multiple linear regression model was formulated. The result of the multiple linear regression analysis revealed that the co-efficient of multiple determination (adjusted R2) was 0.941 which indicated that 94.1 per cent variation in labour use efficiency is explained by the independent variables chosen for the study. The results also revealed that the determinants like source of labour, system of rearing, net profit, quantum of milk produced, herd size and income from dairying positively influenced the labour use efficiency (dependent variable) whereas age of the farmers negatively influenced the labour use efficiency which indicates that farmers become less efficient as they get older. These results suggest that labour use efficiency is better with the farms having large herd size, more family labours, young, averagely educated and rearing cross bred cattle to rise the quantum of milk production which indirectly rise the net profit from dairy farming in Tamil Nadu.
Keywords: Urban Dairy Farming; Labour Use Efficiency; Multiple Linear Regression